Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.29333/iji.2020.13245a
|View full text |Cite
|
Sign up to set email alerts
|

Self Efficacy and Emotional Quotient in Mediating Active Learning Effect on Students’ Learning Outcome

Abstract: The purpose of this study is to analyze the self-efficacy and emotional intelligence in mediating the effect of implementing active learning methods on student learning outcomes. The population of this study is the population in this study were Indonesian language and literature education students in East Java who were taking Indonesian Language courses with a sample size of 160 students. Data analysis in this research uses Structural Equation Modeling. The results showed that the active learning method had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
1
15
0
1
Order By: Relevance
“…Firstly, this study verified that deep learning includes two dimensions, deep information processing, and deep learning investment which proved the rationality of Biggs (1987) definition of deep learning from the model cognitive perspective, and then, this study also proved that deep learning not only includes deep information processing and deep learning investment but also contains the deep cognitive emotional experience and deep learning meta-cognitive participation, thus this study results supported the CAPS theory (Mischel and Shoda, 1995) that emotional factors of students will have an interaction with individuals' cognitive and behavior results to form the individual's inherent learning quality characteristics. Previous similarly studies also supported the current research results, Chong et al (2018) proved that student emotional participation has a significant mediating effect on academic performance, and there is a symbiotic and coordinated relationship between learning emotion and mindful learning (Yanko and Yap, 2020), emotional factors play a significant mediating role between active learning and learning effectiveness (Kustyarini, 2020), all of these studies demonstrated that emotional factors participate in the learning process, therefore the current research conclusions are reasonable, and there is no research to verify whether the deep learning model contains emotional factors from the perspective of theoretical construction, so the current research conclusions are innovative. Furthermore, the research results also supported the selfregulatory executive function (S-REF) model (Lewin, 1935;Murray, 1938Murray, , 1951 that meta-cognitive factor can be used as an important part of the deep learning model which participating in the entire process of students' deep learning investment, deep information processing, and deep cognitive emotional experience to maintain students' deep learning state.…”
Section: Discussionsupporting
confidence: 85%
“…Firstly, this study verified that deep learning includes two dimensions, deep information processing, and deep learning investment which proved the rationality of Biggs (1987) definition of deep learning from the model cognitive perspective, and then, this study also proved that deep learning not only includes deep information processing and deep learning investment but also contains the deep cognitive emotional experience and deep learning meta-cognitive participation, thus this study results supported the CAPS theory (Mischel and Shoda, 1995) that emotional factors of students will have an interaction with individuals' cognitive and behavior results to form the individual's inherent learning quality characteristics. Previous similarly studies also supported the current research results, Chong et al (2018) proved that student emotional participation has a significant mediating effect on academic performance, and there is a symbiotic and coordinated relationship between learning emotion and mindful learning (Yanko and Yap, 2020), emotional factors play a significant mediating role between active learning and learning effectiveness (Kustyarini, 2020), all of these studies demonstrated that emotional factors participate in the learning process, therefore the current research conclusions are reasonable, and there is no research to verify whether the deep learning model contains emotional factors from the perspective of theoretical construction, so the current research conclusions are innovative. Furthermore, the research results also supported the selfregulatory executive function (S-REF) model (Lewin, 1935;Murray, 1938Murray, , 1951 that meta-cognitive factor can be used as an important part of the deep learning model which participating in the entire process of students' deep learning investment, deep information processing, and deep cognitive emotional experience to maintain students' deep learning state.…”
Section: Discussionsupporting
confidence: 85%
“…The results of this study are also under research conducted by Kustyarini (2020), which asserted that the teachers who have emotional intelligence could develop learners to recognize themselves and others so that they can raise their self-confidence to have high independence in the learning process. The emotional intelligence possessed by the teacher can develop the individual academic abilities and the development of social aspects, as well as build team collaboration and good learning interaction with teachers and learners (Noer, Tambak & Rahman, 2017.…”
Section: The Influence Of Islamic Psychosocial On Learning Assessment Of Madrasah Aliyah Teachersmentioning
confidence: 74%
“…Learning outcomes can be characterized as the scores received by students in tests which are the values of their efficiency and results achieved in the learning procedure (Kustyarini, 2020). Learning outcomes are the abilities that students possess in the learning process, which are divided into five main parts: (1) intellectual skills, (2) cognitive strategies, (3) language information, (4) motor skills, and (5) attitudes, and they could provide the value of measuring alternative methods under different conditions because there are tangible and desirable results (Kustyarini, 2020). The core issue with the wide application of online learning is the confusion of its effectiveness compared to traditional learning.…”
Section: Learning Outcomesmentioning
confidence: 99%